(untitled) (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
This scientific article is devoted to the analysis of the research of a prominent specialist in Kazakh linguistics, Corresponding member of the kazakh academy of education, Honored Worker of education of the Republic of Kazakhstan, Distinguished educator of the USSR, candidate of philological sciences, professor Kinyat Shayakhmetuly. The scholar is widely recognized in the academic community for his fundamental studies in Kazakh linguistics, turkology, general linguistics, and methods of teaching language and literature. The article emphasizes that the researcher’s works are distinguished by their innovative character, conceptual and methodological depth, and have made a significant contribution to the development of linguistic science. These studies address issues of theoretical and applied linguistics, sociolinguistics, and general linguistics within the framework of the interaction of word formation and inflection systems (derivatology and morphology). The aim of the study is to substantiate the continuity of the scholar’s achievements in various fields of linguistics with both global and national linguistic traditions, as well as to trace the dynamics of their development. The relevance of the article is determined by the need for a critical assessment and synthesis of research results in linguistics from the standpoint of modern interdisciplinary approaches to the analysis of linguistic and extralinguistic processes. It is concluded that K. Shayakhmetuly made a significant contribution to the formation of modern linguistic science. He expanded the scope of research from the grammatical framework of Kazakh linguistics to the study of contemporary processes of linguistic cognition, ethnocognition, and lexical cognition. In conclusion, it is noted that the scholar’s published works have enriched the tools of linguistics with new approaches and significantly broadened the horizons of scientific inquiry. It is emphasized that K. Shayakhmetuly is a distinctive linguistic personality who has developed his own scientific conception.